Differentiate y=(x^2+1)(e^-x)

Here, we're using the product rule (and the chain rule for the e-x): y=(x2+1)(e-x) dy/dx=(2x)(e-x)+(x2+1)(-1)(e-x) Then we simplify to get: dy/dx=(e-x)(2x-x2-1)

Answered by Rishav D. Maths tutor

6237 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

If f(x) = sin(2x)/(x^2) find f'(x)


Differentiate 2^x


The function f is defined for all real values of x as f(x) = c + 8x - x^2, where c is a constant. Given that the range of f is f(x) <= 19, find the value of c. Given instead that ff(2) = 8, find the possible values of c.


Differentiate: ln((e^x+1)/e^x-1))


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences